2011
DOI: 10.1586/ecp.10.125
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide in the endocrine and reproductive systems

Abstract: Hydrogen sulfide (H(2)S) is now considered a member of a group of signaling molecules termed 'gasotransmitters'. H(2)S has been shown to be generated in the endocrine and reproductive organs and elicits various actions. H(2)S modulates insulin secretion in pancreatic islets. Adipose tissues have the ability to produce H(2)S, which regulates the local insulin sensitivity and vascular responsiveness. H(2)S also acts on the hypothalamic-pituitary-adrenal axis and is involved in stress responses. The effects of H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…It has various effects such as antioxidant, anti-inflammatory and anti-apoptotic in different parts of body (Yonezawa et al, 2007). In addition, it has the main role in corpus cavernosum as a mediator of smooth muscle relaxation and can be found in vas deferens and prostate tissues (Zhu, Gu, & Ni, 2011). It was reported that CSE is expressed in sertoli cells, spermatogonia and epididymis of rats.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has various effects such as antioxidant, anti-inflammatory and anti-apoptotic in different parts of body (Yonezawa et al, 2007). In addition, it has the main role in corpus cavernosum as a mediator of smooth muscle relaxation and can be found in vas deferens and prostate tissues (Zhu, Gu, & Ni, 2011). It was reported that CSE is expressed in sertoli cells, spermatogonia and epididymis of rats.…”
mentioning
confidence: 99%
“…H 2 S can be produced by different enzymes including cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3MST) (Kimura, 2013). Several studies have demonstrated the protective effects of H 2 S on disorders such as renal and reproductive system diseases (Lobb et al, 2014;Zhu et al, 2011). In addition, it has the main role in corpus cavernosum as a mediator of smooth muscle relaxation and can be found in vas deferens and prostate tissues (Zhu, Gu, & Ni, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S, a colorless, flammable, and foul odored gas, has been considered poisonous for a long time1022. Recently, it has been found to be a signaling molecule regulating insulin secretion/sensitivity and vascular homeostasis to control blood pressure and penile tone102223. Furthermore, it is a mediator of dietary restriction24.…”
mentioning
confidence: 99%
“…H 2 S biosynthesis in mammals is catalyzed by cystathionine β-synthase, cystathionine γ-lyase, and 3-mercaptopyruvate sulfurtransferase. 3,4 H 2 S signaling is implicated in numerous cellular processes 57 and plays an especially important role in the cardiovascular system where the gasotransmitter protects against ischemia/reperfusion injury, regulates blood pressure, promotes angiogenesis, and inhibits plaque formation. 811 H 2 S also acts as a neuromodulator/neuroprotectant and an oxygen sensor and can induce hibernation-like states in mice.…”
mentioning
confidence: 99%